Training For Developing Digital Presences With Zoho Form For Office Automation And Office Governance - Wisudani Rahmaningtyas; Muhsin Muhsin; Ahmad Saeroji (LPPM Universitas Muhammadiyah Tasikmalaya, 2021)
Teachers in facing the challenges of rapid technological advances are expected to always adapt to the times, which are required to always innovate and be creative to be able to create quality graduates. So that students have good provisions in facing the challenges ahead. Teachers who teach at Vocational High Schools majoring in office automation and governance include Office Technology subjects. The Office Technology subject contains practical material regarding the use of applications for office or administrative activities, which as the name suggests is currently the office administration department changed to the office automation and governance department. However, the applications used for learning related to the use of applications and the application of digital offices, especially the creation of digital presences to switch to paperless, are still very minimal or even non-existent. Learning office technology, which has been difficult for teachers to provide and provide skills to students related to applications that support the digitization of offices through office technology subjects. In the era of computerization, it affects administrative management in an organization, as well as a student majoring in office automation and governance must have competence in mastering digitalization and office automation skills.